Philippine English development, structure and sociology of English in the Philippines - Borlongan, Ariane Macalinga (Abingdon, Oxon New York, NY Routledge, 2023)
"Philippine English is a comprehensive reference work on the history, sociology, and linguistic structure of Philippine English. It offers readers unprecedented access to a synthesis of the last fifty years of research into Philippine English as well as putting forward a new and better understanding of the phenomenon of the nativization of English in the Philippines and the emergence of Philippine English. This definitive resource covers in great length and depth all that is currently known about the new English. The chapters offer detailed descriptions of Philippine English at various linguistic levels in addition to examining the sociolinguistic factors which shaped the language. Offering discussions of practice, language policy, language education, language teaching, and the relevance of English in various social phenomena in the Philippines, readers will find everything they need to know on theory, methodology, and application in the study of Philippine English"--
Preface / Ariane Macalinga Borlongan -- Deconstructing Ma. Lourdes Bautista: a non-linguist's perspective / Tereso S. Tullao, Jr. -- Prologue: Philippine English in the 'concerto' of world Englishes / Edgar W. Schneider -- Introduction. Conspectus / Ariane Macalinga Borlongan -- History / Ariane Macalinga Borlongan -- Resources / Dominik Heps and Mikhail Alic C. Go -- Ma. Lourdes Bautista and Philippine English / Anne Pakir -- Linguistic structure. Phonology / Irwan Shah Shahruddin, Ran Ao and Ee Ling Low -- Lexicon / Thomas Biermeier -- Grammar / Philip Rentillo, Shirley N. Dita and Aldrin P. Lee -- Discourse / Marilu R. Madrunio -- Spelling and punctuation / Robert Fuchs -- Sociolinguistic variation and change. Internal variation / Aldrin P. Lee and Ariane Macalinga Borlongan -- Diachronic change / Ariane Macalinga Borlongan and Peter Collins -- Philippine English in relation to American English / Edgar W. Schneider -- Contact with other languages / Ma. Althea T. Enriquez -- Hybridization / Wilkinson Daniel Wong Gonzales -- Linguistic and literary canon. Lexicography / Danica Salazar -- Standard Philippine English / Ariane Macalinga Borlongan -- Philippine Literature in English / Isagani R. Cruz -- Psychosociolinguistic dimensions. Intelligibility / Shirley N. Dita and Kristine D. de Leon -- Attitudes / Philip Rentillo -- Multilingualism / Loy Lising -- Language policy / Ruanni Tupas -- Learning and teaching. Acquisition and learning / Aireen Barrios -- Language teaching / Alejandro S. Bernardo -- Language testing / Dave Kenneth Cayado and James D'Angelo -- Teacher education / Edward Jay M. Quinto and Sterling M. Plata -- Contemporary issues. Internet / Leah E. Gustilo and Chenee M. Dino -- Migration / Beatriz P. Lorente -- Outsourced call centers / Eric Friginal and Rachelle Friginal -- Teaching English as a foreign language in the Philippines / Aiden Yeh -- Special feature: World Englishes and social change / Ahmar Mahboob -- Epilogue: Contemporary concerns and future directions / Kingsley Bolton.
Includes bibliographical references and index.
Keywords: English language -- Philippines